THE ANALYSIS OF EXPERIENCE OF DEVELOPED COUNTRIES IN THE APPLIANCE OF STATE SUPPORT IN THE SYSTEM OF MANAGEMENT AND AGRICULTURAL DEVELOPMENT - G. Fyliuk; O. Pimenova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The role of state support in enhancing of the competitiveness of agricultural sector is determined. Mechanisms of state support of Germany are analyzed. A necessity of use of targeted financial support to the introduction of monitoring systems in domestic agriculture is proved. The questions of financial support for Ukrainian agricultural producers, which carried out in 16 major budget programs that cover all areas of agricultural enterprises, including the provision of interest-free loans to farmers, reduction of bank loans and insurance premiums, to provide assistance in buying of heavy agricultural machinery of domestic production are examined. The international experience of support and regulation of agriculture, including studies of state support of agriculture in Germany, which allows to solve the problems of agriculture, including efficient use of agricultural land, food security and creating a competitive market for agricultural products is overviewed.